Melatonin Treatment Improves Insulin Resistance and Pigmentation in Obese Patients with Acanthosis Nigricans - Hang Sun; Xingchun Wang; Jiaqi Chen; Aaron M. Gusdon; Kexiu Song; Liang Li; Shen Qu (International Journal of Endocrinology)
Objective. This study aimed to determine the effects of melatonin on insulin resistance in obese patients with acanthosis nigricans (AN). Methods. A total of 17 obese patients with acanthosis nigricans were recruited in a 12-week pilot open trial. Insulin sensitivity, glucose metabolism, inflammatory factors, and other biochemical parameters before and after the administration of melatonin were measured. Results. After 12 weeks of treatment with melatonin (3 mg/day), homeostasis model assessment insulin resistance index (HOMA-IR) (8.99 ± 5.10 versus 7.77 ± 5.21, p<0.05) and fasting insulin (37.09 5 ± 20.26 μU/ml versus 32.10 ± 20.29 μU/ml, p<0.05) were significantly decreased. Matsuda index (2.82 ± 1.54 versus 3.74 ± 2.02, p<0.05) was significantly increased. There were also statistically significant declines in the AN scores of the neck and axilla, body weight, body mass index, body fat, visceral index, neck circumference, waist circumference, and inflammatory markers. Conclusions. It was concluded that melatonin could improve cutaneous symptoms in obese patients with acanthosis nigricans by improving insulin sensitivity and inflammatory status. This trial is registered with ClinicalTrials.gov NCT02604095.